2022
DOI: 10.1161/circ.145.suppl_1.058
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 058: Subclinical Myocardial Injury, Coagulopathy, And Inflammation In Covid-19: A Meta-analysis

Abstract: Introduction: Infection with the SARS-CoV-2 virus can lead to myocardial injury, with cardiac biomarker elevations. Objective: To quantify the association between biomarkers of myocardial injury, coagulation, and severe COVID-19 and death in hospitalized patients. Methods: Studies were identified from PubMed, Embase, CINAHL, Cochrane, Web of Science, and Scopus, published between December 2019 to August 2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study team observed a high prevalence of comorbid conditions (hypertension/T2D) in the sample and found elevated biomarkers to be significantly associated with severe COVID‐19 and death. 58 …”
Section: Oral Abstract Presentationsmentioning
confidence: 99%
“…The study team observed a high prevalence of comorbid conditions (hypertension/T2D) in the sample and found elevated biomarkers to be significantly associated with severe COVID‐19 and death. 58 …”
Section: Oral Abstract Presentationsmentioning
confidence: 99%